The Kids Insight into Dementia Survey (KIDS): development and preliminary psychometric properties. (3rd August 2018) - Baker, Jess R.; Low, Lee-Fay; Goodenough, Belinda; Jeon, Yun-Hee; Tsang, Ruby S. M.; Bryden, Christine; Hutchinson, Karen
ABSTRACT: Objectives: Children may have a foundational role in efforts to raise community awareness about dementia. There is some qualitative work with children with a relative with dementia, but little work into the insights of children as general citizens without affected family. One issue is an absence of measurement tools; thus the study aimed to design and pilot a psychometrically sound self-report measure of dementia attitudes for children. Method: Using a multi-staged scale development process, stakeholder and expert input informed a 52-item Kids Insight into Dementia Survey (KIDS). After a pretest of KIDS with 21 Australian schoolchildren aged 10–12 years, exploratory factor analysis and reliability and validity testing were run on a revised KIDS with data from 203 similar-aged schoolchildren. Results: The KIDS was reduced from 52 to 14 items, and a three-factor solution identified: 'Personhood, ' 'Stigma, ' and 'Dementia Understanding.' A strong positive correlation with an adult measure of dementia attitudes ( r = .76) and a moderate positive correlation with a child measure of attitudes towards older adults ( r = .47) indicated good concurrent validity. Internal consistency of .83 indicated good reliability. Conclusion: Results support the use of KIDS as a tool to measure children's insight into dementia, and to evaluate dementia education initiatives targeting the youth.